Zinc Oxide Nanoparticle Synergizes Sorafenib Anticancer Efficacy with Minimizing Its Cytotoxicity. (29th May 2020) - Nabil, Ahmed; Elshemy, Mohamed M.; Asem, Medhat; Abdel-Motaal, Marwa; Gomaa, Heba F.; Zahran, Faten; Uto, Koichiro; Ebara, Mitsuhiro
Abstract : Cancer, as a group, represents the most important cause of death worldwide. Unfortunately, the available therapeutic approaches of cancer including surgery, chemotherapy, radiotherapy, and immunotherapy are unsatisfactory and represent a great challenge as many patients have cancer recurrence and severe side effects. Methotrexate (MTX) is a well-established (antineoplastic or cytotoxic) chemotherapy and immunosuppressant drug used to treat different types of cancer, but its usage requires high doses causing severe side effects. Therefore, we need a novel drug with high antitumor efficacy in addition to safety. The aim of this study was the evaluation of the antitumor efficacy of zinc oxide nanoparticle (ZnO-NPs) and sorafenib alone or in combination on solid Ehrlich carcinoma (SEC) in mice. Sixty adult female Swiss-albino mice were divided equally into 6 groups as follows: control, SEC, MTX, ZnO-NPs, sorafenib, and ZnO-NPs+sorafenib; all treatments continued for 4 weeks. ZnO-NPs were characterized by TEM, zeta potential, and SEM mapping. Data showed that ZnO-NPs synergized with sorafenib as a combination therapy to execute more effective and safer anticancer activity compared to monotherapy as showed by a significant reduction (P < 0.001 ) in tumor weight, tumor cell viability, and cancer tissue glutathione amount as well as by significant increase (P < 0.001 ) in tumor growth inhibition rate, DNA fragmentation, reactive oxygen species generation, the release of cytochrome c, and expression of the apoptotic gene caspase-3 in the tumor tissues with minimal changes in the liver, renal, and hematological parameters. Therefore, we suggest that ZnO-NPs might be a safe candidate in combination with sorafenib as a more potent anticancer. The safety of this combined treatment may allow its use in clinical trials.